Framing Analysis of Stunting News in Prokopim Ponorogo and Madiun - Anggraini, Novita; Kriyantono, Rachmat; Wulandari , Maulina Pia (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2024)
This study aims to dissect the completeness of the news using syntactic, script, thematic and rhetorical structure analysis through analysis on the Prokopim Ponorogo Regency and Prokopim Madiun Regency websites. In recent years, online mass media has grown significantly, providing local governments with new ways to communicate with the public such as building communication on websites. Mass media websites reflect dynamic and open communication strategies, offering great opportunities for local governments to achieve objectivity and communicate with the public. Functioning as the main tool in public relations practices at the district level, websites play an important role as interactive platforms that influence the relationship between the district government and the community. Framing, as an integral part of PR, helps organizations shape and establish reality through perspectives on the external environment. By utilizing the framing analysis method of Zhondang Pan and Gerald M. Kosicki, this study produces findings in the form of similarities and differences in news framing. Both use an inverted pyramid approach in news structure and present news with 5W + 1H elements. However, there are differences in framing construction in both media in reporting, such as the structure and use of words in the news. Overall, these differences in framing can influence the socio-psychological conditions of the Madiun and Ponorogo communities.